Struggling to fight managerial opportunism in nineteenth- century Europe. Issue 4 (1st October 2016) - Brockhoff, Klaus
Abstract: During the second half of the nineteenth century, a growing interest in joint-stock corporations emerged. At the same time, managerial opportunism was observed in many of these corporations. Inefficient capital markets and inadequate transparency of operations as well as their results were characteristics of the time. Little was known about the means to reduce this opportunism. This knowledge grew over time out of pragmatic ideas, which foreshadow elements of present day agency theory. The important question to be answered by these pragmatic ideas was how managers could be influenced to act according to the goals of the owners of these corporations. In this paper, we draw on mostly academic literature of the nineteenth century to illustrate the developments of such pragmatic ideas. The presentation is structured by major mechanisms of agency theory. It is shown that attempts at reducing asymmetry of information by limiting corporate activities to less risky business, belief in high moral standards of managers or governmental supervision of operational activities were basically unsuccessful ideas. However, the empowerment of shareholders by introducing a supervisory board and the offering of monetary incentives showed more promise. Obviously, these ideas were not perfect. The pros and cons of any of these instruments became more visible over time, which led to better legal structures for establishing supervisory boards. With respect to monetary incentives, the contemporary debates seem to have been quite enlightened as compared with recent discussions.